Evaluating and Prioritizing Circular Supply Chain Alternatives in the Energy Context with a Holistic Multi-Indicator Decision Support System - Thanh Quang Nguyen; Sonia Longo; Maurizio Cellura; Le Quyen Luu; Alessandra Bertoli; Letizia Bua (Energies)
Transitioning to a circular economy is crucial for sustainable energy development; yet, current energy supply chains lack comprehensive assessment tools. This study introduces the Holistic Multi-Indicator Decision Support System (HMI_DSS), an innovative tool grounded in life cycle thinking and advanced multi-criteria decision-making methodologies, including Entropy and PROMETHEE II. The HMI_DSS quantifies and assesses sustainability and circularity in energy systems by employing 49 indicators, with a focus on energy efficiency and greenhouse gas emissions. A case study on the rice straw energy supply chain for biogas production illustrates the tool’s effectiveness, comparing a baseline scenario to an alternative. The results show that the global warming potential (GWP) of the baseline is 122 gCO2eq/kWh, while the alternative is 116 gCO2eq/kWh. However, the baseline scenario has lower energy consumption (1.72 × 107 MJ annually) than the alternative (1.98 × 107 MJ). Overall, the alternative outperforms the baseline in terms of sustainability and circularity. The HMI_DSS offers a flexible and robust framework for evaluating trade-offs in energy systems, providing valuable insights for energy companies and researchers in adopting circular economy principles to achieve sustainable development.